Working knowledge employee innovation and the rise of corporate intellectual property, 1800-1930 - Fisk, Catherine L., 1961-; American Society for Legal History (Chapel Hill, [N.C.] : University of North Carolina Press, 2009)
Skilled workers of the early nineteenth century enjoyed a degree of professional independence because workplace knowledge and technical skill were their 'property', or at least their attribute. In most sectors of today's economy, however, it is a fundamental and widely accepted truth that businesses retain legal ownership of employee-generated intellectual property. This book chronicles the legal and social transformations that led to the transfer of ownership of employee innovation from labour to management.
Published in association with the American Society for Legal History.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Inventions, Employees' -- United States -- History; Intellectual property -- United States; Patents and government-developed inventions -- United States; Law; Legal history; Laws of specific jurisdictions & specific areas of law